Creating a Conducive Environment for Deep Learning in the Classroom - Tee, Meng Yew; Karney, Dennis (INTI International University, 2007)
The purpose of this paper is to suggest a way for educators to structure their class to enhance the possibilities for students to develop stronger communication, analytical, critical and creative problem-solving skills – ultimately, characteristics that are essential for employability in the global marketplace. These skills basically give students the ability to learn how to learn, and can be achieved through learning environments and experiences that encourages deep learning. Unfortunately, the classrooms of today are all too often focused on knowledge transmission with little time spent on creating learning conditions that promote deep learning. This can be a result of the mental models of the teacher, having grown up and learned to teach in a world where knowledge transmission was a dominant role of the teacher. This paper – through research-based data and practice wisdom – intends to provide that teacher with a framework and a mental model that can help create opportunities in the classroom for deep learning while not diminishing the necessary knowledge transfer of vital information.